Prophetic Law Accentuation in Marriage Regulations in Indonesia: Efforts to Maintain Family Resilience During The Pandemic - Adi Nur Rohman (Pandecta Research Law Journal, 2022)
The Indonesian people during the pandemic seemed to forget the purpose of married life which idealizes a household that lasts forever. The increasing divorce rate during the pandemic seems to confirm this hypothesis regardless of any triggering factors. Of course, the product of legislation related to marriage and family must be able to maintain the integrity and resilience of the family. This article aims to analyze transcendental values in marriage law regulations which play a very significant role in building family resilience. This article is in the form of a normative legal study that instrumented the approach to the application of laws and the philosophical approach and prophetic legal theory as a knife of analysis. The results of the study show that emphasizing divine values on rules that build and family resilience is absolutely necessary in and maintaining family resilience which is manifested in a sakinah, mawaddah and rahmah household. Prophetic values such as efforts to complicate divorce, legalization of marriages based on religious law, marriage as a form of lifelong ubudiyah must be internalized in applicable legal regulations.